2019
DOI: 10.1016/j.btre.2019.e00347
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile (HPLC-UV) of olive leaves according to extraction procedure and assessment of antibacterial activity

Abstract: Highlights High recovery of olive leaves phenolics via maceration in ethanol-distilled water. Oleuropein is the major compound of extraction with ethanol-distilled water. Phenolics and flavonoids were better recovered from dried than fresh leaves. Caffeic and ferulic acids weren’t detected in fresh leaves compared to dried ones. Ethanol-distilled water extract has antibacterial effect against bacteria tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 18 publications
11
68
3
Order By: Relevance
“…The authors, contrarily to us, finally established that water was not a good solvent to extract Olp from olive leaves. The Olp concentration in MF, O, and U water resulted also much higher than that reported by Ghomariet al [48] when cold distilled water was used for the extraction (about 100 mg/kg). On the other hand, higher Olp concentrations were detected by using distilled water at 60 °C (19.3 ± 0.99 mg/g) and distilled water at 60 °C and pH 3 (23.36 ± 0.91 mg/g) [48].…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The authors, contrarily to us, finally established that water was not a good solvent to extract Olp from olive leaves. The Olp concentration in MF, O, and U water resulted also much higher than that reported by Ghomariet al [48] when cold distilled water was used for the extraction (about 100 mg/kg). On the other hand, higher Olp concentrations were detected by using distilled water at 60 °C (19.3 ± 0.99 mg/g) and distilled water at 60 °C and pH 3 (23.36 ± 0.91 mg/g) [48].…”
Section: Resultscontrasting
confidence: 49%
“…The Olp concentration in MF, O, and U water resulted also much higher than that reported by Ghomariet al [48] when cold distilled water was used for the extraction (about 100 mg/kg). On the other hand, higher Olp concentrations were detected by using distilled water at 60 °C (19.3 ± 0.99 mg/g) and distilled water at 60 °C and pH 3 (23.36 ± 0.91 mg/g) [48]. Similarly, Ansari et al [40] reported that distilled water at 60 °C and pH 3 for 4 h could allow the extraction of a large amount of Olp.…”
Section: Resultscontrasting
confidence: 49%
“…The amounts of hydroxytyrosol, luteolin and rutin were found less than 2.0 mg/g. In another report, they analyzed the olive leaf samples extracted with different solvents (80% ethanol, 20% acetonitrile, and distilled water) by using an HPLC-UV method [18]. For the sample extracted with 80% ethanol, oleuropein (29.5 mg/g) was found the major compound.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, the usage of olive leaves was emphasized as an antioxidant source in pharmaceuticals [23]. Ghomari and co-workers worked on antibacterial activities of phenolic compounds against pathogenic bacteria and demonstrated that oleuropein showed a strong antibacterial activity [18]. It has been demonstrated that olive phenolic compounds, especially oleuropein or hydroxytyrosol exhibit L-type Ca 2+ channel antagonistic effects [24] and protect against vascular risk through the down-regulation of adhesion molecules [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial activity is another very important property of the compounds present in olive leaves. Some authors have reported activity against bacteria, such as Escherichia coli, Staphylococcus aureus, Campylobacter jejuni, Listeria monocytogenes e Salmonella spp., among others (Sudjana et al, 2009;Rafiei et al, 2012;Ghomari et al, 2019 ;Bayram et al, 2020).…”
Section: Introductionmentioning
confidence: 93%